Type 2 Diabetes Mellitus is the Risk Factor for Multi-drug Resistance Tuberculosis: A Meta-Analysis - Bibit Irawan; Farit Setyo Nugroho; Nine Elissa Maharani (Journal of Epidemiology and Public Health, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) has a significant risk of developing active Tuber-culosis (TB) and complicates its treatment. There is no conclusive evidence on whether TB-T2DM comorbidities are associated with an increased risk of Multidrug Resistant Tuberculosis (MDR-TB). The study aims to analyze and estimate the relationship of T2DM to MDR-TB incidence and to estimate the size of the combined effect. Subjects and Method: This study was a meta-analysis with PICO, Population: patients actively undergoing MDR-TB treatment. Intervention: Patients with comorbid Type 2 Diabetes Mellitus. Comparison: Tuberculosis patients without comorbid Type 2 diabetes mellitus. Output: MDR-TB (Multidrug Resistant Tuberculosis). The articles used in this study were obtained from databases with keywords to search for articles were ("Diabetes Mellitus, Type 2" OR "diabetic" OR "diabetes") AND "tuberculosis" AND ("Tuberculosis, Multidrug-Resistant" OR "drug resistance" OR "multidrug-resistant" OR "multidrug resistant" OR "multidrug resistance" OR "drug-resistant" OR "drug resistant"). Articles were selected based on inclusion criteria, is published in the form of an English full-text article from January 2015 to January 2025, reporting the relationship between T2DM and MDR-TB among TB patients. The articles were selected using the PRISMA flow diagram and analyzed using the Review Manager 5.3 application. Results: This meta-analysis consisted of 9 articles originating from Europe, Asia, Africa and America. Results of the meta-analysis showed that the cohort study of type 2 diabetes mellitus had a 4.11 times greater risk of developing MDR-TB compared to people who did not have type 2 diabetes mellitus. In a control case study of type 2 diabetes mellitus, there was a 3.11 times greater risk of developing MDR-TB than people without type 2 diabetes mellitus, and both were statistically significant (aOR= 3.39; CI 95%= 2.05 to 8.24; p= 0.001). Conclusion: Type 2 diabetes mellitus is a risk factor for MDR TB.